2011
DOI: 10.1101/lm.2101411
|View full text |Cite
|
Sign up to set email alerts
|

Cellular site and molecular mode of synapsin action in associative learning

Abstract: Synapsin is an evolutionarily conserved, presynaptic vesicular phosphoprotein. Here, we ask where and how synapsin functions in associative behavioral plasticity. Upon loss or reduction of synapsin in a deletion mutant or via RNAi, respectively, Drosophila larvae are impaired in odor-sugar associative learning. Acute global expression of synapsin and local expression in only the mushroom body, a third-order "cortical" brain region, fully restores associative ability in the mutant. No rescue is found by synapsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 81 publications
3
55
0
Order By: Relevance
“…We tackle this issue using odour-sugar associative conditioning in larval Drosophila (Fig.1A) (Scherer et al, 2003;Michels et al, 2005;Neuser et al, 2005;Mishra et al, 2010;Chen et al, 2011;Michels et al, 2011;Saumweber et al, 2011a;Saumweber et al, 2011b) (for reviews, see Gerber and Stocker, 2007;Gerber et al, 2009;Diegelmann et al, 2013). This is a suitable system for such a study due to its simplicity in terms of cell number, its genetic tractability and the robustness of the paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…We tackle this issue using odour-sugar associative conditioning in larval Drosophila (Fig.1A) (Scherer et al, 2003;Michels et al, 2005;Neuser et al, 2005;Mishra et al, 2010;Chen et al, 2011;Michels et al, 2011;Saumweber et al, 2011a;Saumweber et al, 2011b) (for reviews, see Gerber and Stocker, 2007;Gerber et al, 2009;Diegelmann et al, 2013). This is a suitable system for such a study due to its simplicity in terms of cell number, its genetic tractability and the robustness of the paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…S1A,B). Comparing our procedures to the published ones, however, revealed that we had used a substantially lower concentration of n-amylacetate (AM) (a 1:1600 dilution rather than the 1:50 dilution of AM used in both Michels et al 2005Michels et al , 2011. Subsequently using the higher concentration of AM (1:50), the published defect of the syn 97 mutant was reproduced (Supplemental Fig.…”
mentioning
confidence: 92%
“…In Drosophila, Synapsin is encoded by only one gene and is expressed in most if not all neurons of both the larval and adult nervous system (coding gene: syn, CG 3985: Klagges et al 1996;Michels et al 2005). Both adult and larval Drosophila lacking Synapsin show associative memory scores that are reduced by about half as compared with wild-type animals, as do animals upon an RNAi-mediated knockdown of Synapsin (adult odor-punishment memory: Godenschwege et al 2004;Knapek et al 2010;Niewalda et al 2015;Walkinshaw et al 2015; larval odor-reward memory: Michels et al 2005Michels et al , 2011. Corresponding phenotypes in learning and memory tasks have been reported throughout the animal kingdom, including man (Silva et al 1996;Garcia et al 2004;Südhof, 2004;Gitler et al 2008;Greco et al 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations